Psychiatric symptoms of Turkish combat-injured non-professional veterans - Berna Güloğlu (European Journal of Psychotraumatology, 2016)
Background: It is well-known that exposure to combat puts individuals at risk for developing adverse psychological problems, including posttraumatic stress disorder (PTSD), depression, anxiety, and health-related behaviour problems and that the presence of combat-related injury increases the risk for psychopathology. Little is known, however, about the consequences of combat among conscripted soldiers fighting against terrorism in their homeland. Objective: The main aim of the current study was to examine the prevalence of probable PTSD, severity of PTSD symptoms, depression, anxiety, and PTSD-related functional impairment among Turkish combat-injured, non-professional veterans. In addition, investigated were also the possible differences among the symptoms of PTSD, depression, and anxiety of the veterans by the frequency of current cigarette and alcohol use. Methods: A total of 366 male veterans were assessed by using a demographic information form, which obtained information about injury status and health behaviours, the Posttraumatic Stress Diagnostic Scale (PDS), and the Brief Symptom Inventory (BSI). Symptom frequency and multivariate analysis of variances (MANOVA) were used to analyse the data. Results: The prevalence of probable PTSD was 46.7% (171) among Turkish veterans while 16.4% experienced severe depression and 18% experienced severe anxiety. “Upset at reminders (65.8%)” was the most common PTSD symptom. “Responsibilities related to home (48.4%)” was the most frequently reported PTSD-related functional impairment. Results indicated that veterans who smoke more than half a pack per day scored significantly higher in severity of PTSD symptoms, depression, and anxiety. Contrary to expectations, there was no significant difference in symptoms of PTSD, depression, and anxiety related to the frequency of current alcohol use. Conclusion: Turkish non-professional veterans with physical injuries have serious psychiatric problems an average of 13 years after a combat experience. Psychiatric and psychosocial services to Turkish non-professional veterans are a substantial and ongoing need.